English loanwords in the Icelandic language of the sea. Particularly in the jargon of trawlermen - Sverrir H. Konráðsson 1953- (2005)
The thesis is an analysis of 46 English borrowings adopted by Icelandic seamen during the last decade of the 19th century and the first part of the 20th century when trawling was introduced in Iceland and Icelanders learned this revolutionary fishing method from British seamen. These loanwords have become a part of the Icelandic vocabulary of the sea despite attempts by language purists ashore to cleanse it of the English borrowings. According to a survey conducted in connection with the writing of this thesis, most of the terms are still used on board modern stern trawlers and an attempt to coin neologisms for many of the terms proved unsuccessful, as they never gained any popularity among seamen. By going through the archive of citation slips of the Institute of Lexicography at the University of Iceland and studying written sources on the subject of trawling an attempt was made to determine each term’s first occurrence in the written Icelandic language. A part of the dissertation is an overview of linguistic purism in Iceland and tells the story of an attempt by scholars and governmental officials, who were worried about the influx of a foreign vocabulary into the maritime industries, to cleanse the language by, among other things, forming a terminological committee of academics and professional specialists and compiling lists of acceptable Icelandic terms. Some thoughts are put forward in support of the argument that loanwords have a stimulating effect on the functionality and viability of a language. Finally, the thesis raises the question of whether attempts to cleanse a language of loanwords and foreign influence are likely to affect the language in the long run or not.